The pathological narcissism inventory (PNI) in transitional post-war Croatia: psychometric and cultural considerations - Jakšić, Nenad (Array, 2014)
The Pathological Narcissism Inventory (PNI) is a recently developed measure for assessing randiose and vulnerable themes of narcissistic pathology. The aim of this study was to validate the PNI in the transitional post-war Croatian society by examining its psychometric properties and factor structure in a sample of Croatian university students (N=651). The participants filled out several self-report measures of narcissism, as well as measures of trait emotional stability and negative emotional states. Findings of this study supported the existence of seven first-order and two second-order factors of the PNI, invariant across genders. Additionally, all the subscales had good reliability coefficients, while the associations with other measures supported the concurrent validity of the instrument. These findings support the use of the PNI in a transitional post-war society and emphasize certain aspects of cross-cultural stability of pathological narcissism, although some crosscultural variants should be considered when applying this measure in different cultural settings.